Quantifying the porosity of natural reservoirs with nuclear magnetic resonance - Navarro Pérez, Daniela Josefina (My University, 2023)
Daniela Navarro-Perez explains how nuclear magnetic resonance can be used to assess the capacity of natural reservoirs to store fluids.
Keywords: None